Ideological orientations and left-right self-identifications of young Polish men and women: an image of the political gender-generation gap - Marzęcki Radosław (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2023)
The subject of the author’s interest is the diversity of ideological orientations due to gender and age. The theoretical findings so far indicate that in developed democracies already at the end of the 1990s there was a reversal of the ideological positions of women and men. Recent social research shows that also in Poland women identify with the left to a greater extent than men, and in the younger generation these differences are even greater. The aim of the article is to show in detail the ideological differences between young men and women in Poland. The author poses two types of research questions: (1) descriptive and explanatory, which concern the characteristics of similarities and differences in the ideological orientations of young women and men; (2) methodological, which concern how to measure this phenomenon. The author assumes that the measurement of left-right self-identification used in many studies brings an overly simplified picture of the respondents’ real views, beliefs and values, which can be described as ideological orientations. Therefore, he proposes the use of multidimensional tools (issue-based scale) that allow to better describe complex political attitudes. In search of answers, the author analyzes data from his own survey conducted among a large group of Polish students. Przedmiotem zainteresowań jest różnorodność orientacji ideologicznych ze względu na płeć i wiek. Dotychczasowe ustalenia teoretyczne wskazują, że w rozwiniętych demokracjach już pod koniec lat 90. doszło do odwrócenia pozycji ideologicznych kobiet i mężczyzn. Z ostatnich badań społecznych wynika, że także w Polsce kobiety w większym stopniu niż mężczyźni identyfikują się z lewicą, a w młodszym pokoleniu różnice te są jeszcze większe. Celem artykułu jest szczegółowe ukazanie różnic ideowych pomiędzy młodymi mężczyznami i kobietami w Polsce. Autor stawia dwa typy pytań badawczych: (1) opisowe i wyjaśniające, które dotyczą charakterystyki podobieństw i różnic w orientacjach ideologicznych młodych kobiet i mężczyzn; (2) metodologiczne, które dotyczą sposobu pomiaru tego zjawiska. Autor wychodzi z założenia, że stosowany w wielu badaniach pomiar lewicowo-prawicowej samoidentyfikacji daje nadmiernie uproszczony obraz rzeczywistych poglądów, przekonań i wartości respondentów, które można określić mianem orientacji ideologicznych. Dlatego proponuje zastosowanie narzędzi wielowymiarowych (skala problemowa), które pozwalają lepiej opisać złożone postawy polityczne. W poszukiwaniu odpowiedzi autor analizuje dane z własnego badania przeprowadzonego wśród dużej grupy polskich studentów.
Orientacje ideologiczne i lewicowo-prawicowa samoidentyfikacja młodych Polek i Polaków: obraz politycznej przepaści płciowo-pokoleniowej
Keywords: ideological orientations; left; right; young people; gender-generation gap; orientacje ideologiczne; lewica; prawica; młodzież; różnica pokoleń